Internal marketing determinants of job satisfaction in service companies, first half of 2024 in Tegucigalpa, Honduras - Flores Huete, Fernando (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To identify the determining factors for understanding Internal Marketing levels in service sector companies in Tegucigalpa, Honduras. Specifically, we sought to evaluate the influence of communication, motivation, and income as key variables in job satisfaction.MATERIAL AND METHOD: This study was descriptive in scope, with a non-experimental design and a quantitative approach. A stratified probability sampling framework was used to select participants.Using cross-variable analysis, the possible influence of factors such as age on job performance was examined.RESULTS: According to employee perceptions, service companies maintain effective communication at both the organizational and interdepartmental levels. This study is anticipated to be significantly relevant to companies in Tegucigalpa in relation to the three variables analyzed.CONCLUSIONS: Although the concept of Internal Marketing is not widely recognized as a formal theory in service companies in Tegucigalpa, its empirical application is evident. Therefore, we conclude that there is a need to formalize the implementation of Internal Marketing strategies in these organizations.
Keywords: internal marketing; communication; revenue; motivation; endomarketing.